EFFECTIVENESS OF TEACHING THROUGH RIDDLE - Nazarova Ra’no Rahimovna (Galaxy International Interdisciplinary Research Journal, 2023)
The purpose of this research is to provide information about the effectiveness of teaching through riddle and incorporating riddles into language teaching activities can make learning more engaging and enjoyable for students while enhancing their vocabulary, comprehension skills, verbal fluency, reading abilities, writing practice, and cultural awareness